THE CURRENT STATE OF DIGITAL TECHNOLOGIES IN THE ENERGY SECTOR AND THE MAIN DIRECTIONS OF THEIR APPLICATION - Meng Xiangfei; Kozin Valeriy; Nurmagambetova Azhar (Research Reviews, 2026)
The energy sector is undergoing significant changes related to the introduction of digital technologies. The development of information systems, artificial intelligence, the Internet of Things, big data, and automated management of energy systems makes it possible to increase the efficiency of energy production, transmission, and distribution, reduce operating costs, and minimize environmental impacts. In the context of global digitalization and the transition to smart grids, the study of the current state of digital technologies in the energy sector and their applications is of particular importance for both the scientific community and industry experts. The relevance of the research is determined by the need to modernize energy infrastructure, increase the reliability of energy supply, optimize costs and integrate renewable energy sources, which is an important factor in the competitiveness of companies in today’s market. The purpose of the study is to analyze the current state of digital technologies in the energy sector and identify promising areas of their application to improve the efficiency and sustainability of energy systems. To achieve this goal, the following tasks were defined: To analyze the current state of digital technologies in the energy sector, to identify their main opportunities and limitations. Identify areas of practical application of digital technologies to optimize the operation of energy infrastructure.